Antenatal Ultrasound Findings from a Fetus that was Ultimately Diagnosed with Pyloric Stenosis in the Mid Neonatal Period: A Case Report - Işık Üstüner; Emine Seda Güvendağ Güven; Evren Üstüner; Ebru Düşünceli Atman; Figen Kır Şahin (Medical Network, 2016)
Infantile hypertrophic pyloric stenosis is the most common surgical cause of vomiting in infants. The pyloric muscle is hypertrophied and the pyloric channel becomes narrow and elongated, causing gastric outlet obstruction. This is a case report of antenatal ultrasound findings from a fetus that was ultimately diagnosed with pyloric stenosis in the mid neonatal period.